Sustainability and design ethics - Russ, Jean; Russ, Thomas H. (Boca Raton, FL : CRC Press, 2019)
Sustainability as a concept remains just as challenging and important today as it was when the first edition of this book was published. The Second Edition of Sustainability and Design Ethics explores the ethical obligations of knowledgeable people such as design professionals, taking into consideration the numerous changes that have taken place in recent years. This book expands the growing discussion on the principles of sustainability to further include the role of businesses and governments and considers the general recognition that modern society has occurred at the expense of nature with significant social and environmental impacts. Are there limits to the individual's ethical obligation? How do such obligations change or adapt to a world of sustainable design? As the shift toward sustainability proceeds, designers' ethical underpinnings will be confronted with a wider range of people and concerns whose interests must be weighed. The design professionals are likely to be among the lead in the shift toward sustainability because of the special knowledge and expertise provided to them by their education, experience, and distinctive position in society. The entire world of design is being reassessed and the guiding principles and ethics of design reflect this change. New to the Second Edition: Expanded international scope that includes a comparison of professional organizations in the EU, Australia, Canada, Japan and China Discusses how cultural differences between the West and China result in different underlying foundations for professional ethics Revised analyses to reflect changes in regulatory and technical areas such as the inevitable rise of artificial intelligence in design Updated arguments reflecting the need for sustainability and the designer's role and obligations Updated references pertaining to the progress of sustainable design and development Sustainability and Design Ethics, Second Edition is an attempt to explore the ideas and principles that might contribute to the thinking of thoughtful design professionals. The emergence of "green" design discussed in this book is used to evidence progress, but also to demonstrate the degree to which more is needed.
1. Why Does Prometheus Suffer? 2. Professional Ethics. 3. Is There an Ethical Obligation to Act Sustainably? 4. The Design Professional and Organizations. 5. The Choice for Sustainability. 6. The Precautionary Principle and Design 7. Flourishing Appendix A. Appendix B.
OCLC-licensed vendor bibliographic record.
Keywords: LAW / Environmental; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Mechanical; Sustainable design -- Moral and ethical aspects; Engineers -- Professional ethics; Environmental protection -- Moral and ethical aspects